Analysis of Factors Causing The Delay of the Storage Tank Project Using Fault Tree Analysis - Abdurrohman, Abdurrohman (IPTEK Journal of Proceedings Series, 2020)
The Storage Tank Project is a national vital object that supports the operational reliability program of the Fuel Oil distribution. But there was a delay in the implementation of work by 31.35%. This research purpose to identify the factors and indicators that cause delays in the storage tank construction project. This research method uses Fault Tree Analysis. Factors and indicators are FTA Event inputs which are then illustrated by FTA diagrams. FTA using Boolean algebra formulation results in a probability value for each Event.Objek research is in the construction Storage tanks in Surabaya. Work items in the research are Foundation work with a weight of 26.50% and Construction Work with a weight of 36.94%. From the results of this research there are two indicators with the largest probability value. First, the Soil Data Report is not suitable for foundation work with a value of 0.968 in the owner's area. Therefore, the owner must be more careful in making design documents, especially on foundation work. Second, the lack of manpower with a probability value of 0.912 in construction work in the Contractor's area. in this case the contractor must ensure that the manpower has the required qualifications. Especially in Welder certification.